KEPENTINGAN KELOMPOK TARGET TERHADAP KINERJA IMPLEMENTASI KEBIJAKAN KESEHATAN IBU DAN ANAK DI PROVINSI EAST NUSA TENGGARA - Florentianus Tat (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
The facts show that the performance of health service policy implementation from the aspect of output and the results of the policy is not in line with expectations. This condition will also have a direct influence on the East Nusa Tenggara Province Human Development Index, which is the order of 32 out of 34 provinces in Indonesia at 68.77. The community is both the executor and the target of health development. The community should have interests in health development so that they can actively participate in the health development activities. The interest of the target group in maternal and child health services is still considered limited. The aim is to get an idea of ​​the magnitude of the influence of the target group's interests on the performance of maternal and child health policies in East Nusa Tenggara. This research uses quantitative methods, conducted in 11 districts, 104 health centers and 235 health workers in East Nusa Tenggara province, collecting data using a questionnaire. The results showed there was a correlation between the variable interests of the target group with the policy implementation performance variables (p = 0.00), the correlation coefficient of 0.457. Correlation shows a positive relationship, the higher the interest of the target group, the higher the performance of the MCH policy. There is a significant influence of the interest of the target group on the performance of MCH policy in East Nusa Tenggara Province (t count = 9.535> t table 1.97). Conclusion the interest of the target group in health services is quite good, the performance of the implementation of the policy category is good and there is a significant and positive influence between the interests of the target group and the performance of the policy implementation. Keywords: target group, Performance of MCH policy implementation.